PENCEGAHAN, PENDETEKSIAN DAN PENGINVESTIGASIAN KECURANGAN KOMPUTER OLEH AUDITOR MELALUI AUDIT SISTEM INFORMASI - Efendi, Muhammad Arief (TEKNOINFO, 2008)
These article was auditors aimed to discover the response of their organizations to the threat of computer fraud. The auditors responsibility within organization for the prevention, detection & investigation of the computer fraud, what the auditor does to prevent computer fraud. Computer fraud was one of the white collar crime in organization I company. Information system audit is one of the important tool for auditor to detect & investigate computer fraud with computer assisted audit technique (CAAT) .Â